2009
DOI: 10.1194/jlr.m800374-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

LXR agonist suppresses atherosclerotic lesion growth and promotes lesion regression in apoE*3Leiden mice: time course and mechanisms

Abstract: The aim of this study was to define the antiatherosclerotic role of liver-X-receptors (LXRs) under lesion progressive and lesion regressive conditions, to establish a temporal line of events, and to gain insights into the mechanisms underlying the anti-atherogenic potency of LXRs. We used apoE*3Leiden (E3L) mice to comprehensively and time-dependently dissect how T0901317, an LXR-agonist, inhibits initiation and progression of atherosclerotic lesions and regresses existing lipid-and macrophage-rich lesions. T0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
61
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
5
61
0
3
Order By: Relevance
“…The present results propose an additional mechanism for LXR-atheroprotection, namely, their stimulation of CD68 + cell emigration from plaques through the induction of Ccr7. LXR-dependent acquisition of CCR7 function in CD68 + plaque cells is also consistent with previous work by us (50) and others (24,48), as well as with the more general finding that the acquisition of migratory ability during differentiation of monocytes to DCs is concomitant with both LXR isoforms being expressed (51, 52).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present results propose an additional mechanism for LXR-atheroprotection, namely, their stimulation of CD68 + cell emigration from plaques through the induction of Ccr7. LXR-dependent acquisition of CCR7 function in CD68 + plaque cells is also consistent with previous work by us (50) and others (24,48), as well as with the more general finding that the acquisition of migratory ability during differentiation of monocytes to DCs is concomitant with both LXR isoforms being expressed (51, 52).…”
Section: Discussionsupporting
confidence: 80%
“…Recently, it has also been shown that LXRs also negatively regulate the inflammatory state of macrophages through effects on toll-like receptors and NF-κB (46,47). Activation of LXRs and absence of LXRs have been shown to promote regression (38,48) and exacerbate progression (39,49), respectively, of atherosclerosis in mouse models. These effects of LXRs have been attributed to the aforementioned roles in RCT and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Reintroducing apolipoprotein E (ApoE) into ApoE 2/2 mice via ApoE gene transfer induces regression (3,4). Furthermore, LXR compounds induce atherosclerotic regression by promoting reverse cholesterol transport in macrophages (5). Another approach to study regression was introduced by Feig et al (6) who used a model in which atherosclerosis-containing aortic segments from ApoE 2/2 mice were transplanted into wild-type recipient mice.…”
mentioning
confidence: 99%
“…Freeman et al show that the liver X receptor (LXR) agonist TO901317 increases the deposition of cholesterol microdomains in the ECM produced by macrophages. It is known that, besides upregulation of ABCA1 and ABCG1, LXR agonists both in vivo and in vitro upregulate apoE expression ( 8 ). Future colocalization experiments with MAb(s) against the microdomains and against apoE in cell cultures and in human lesions could be informative in this respect.…”
mentioning
confidence: 99%